Sonographic Renal Parenchymal Measurements for the Evaluation and Management of Ureteropelvic Junction Obstruction in Children - Kelley, Jeremy C.; White, Jeffrey T.; Goetz, Jessica T.; Romero, Elena; Leslie, Jeffrey A.; Prieto, Juan C. (Frontiers in Pediatrics, 2016)
Purpose: To correlate sonographic renal parenchymal measurements among patients with ureteropelvic junction obstruction (UPJO) labeled Society of Fetal Urology (SFU) hydronephrosis grades 1 to 4 and to examine whether sonographic renal parenchymal measurements could be used to differentiate conservative versus surgical management. Materials and Methods: Retrospective chart review and sonographic renal parenchymal measurements (renal length, medullary pyramid thickness, and renal parenchymal thickness ) were performed in patients with SFU grades 1 to 4 hydronephrosis secondary to UPJO managed between 2009 and 2014. Exclusion criteria included other concomitant genitourinary pathology or incomplete follow-up. Anterior-posterior renal pelvic diameter (APRPD) and radionuclide renography were also evaluated when available. Results: 104 patient with ureteropelvic junction obstruction underwent 244 RBUS (1,464 sonographic renal parenchymal measurements in 488 kidneys). Medullary pyramid thickness and renal parenchymal thickness progressively decreased from SFU grades 1 to 4 (p<0.05). A similar trend was appreciated when comparing SFU grades 1 and 2 vs. 3 and 4, as well as SFU grades 3 vs. 4 (p<0.05). SFU grade 3 and 4 patients who underwent pyeloplasty had longer renal length in comparison to those who were managed conservatively (p<0.02). Conclusions: This is the first study that evaluates these objective, quantifiable sonographic renal parenchymal measurements in children with unilateral UPJO. These sonographic renal parenchymal measurements correlate closely with worsening of hydronephrosis graded by the SFU and APRPD classification systems. Prospective studies are needed to elucidate the role of sonographic renal parenchymal measurements in the management of children with UPJO. □